A pilot study on the epidemiology, diagnosis and characterization of Echinococcus granulosus sensu lato in sheep, goats and dogs in Siirt province of Türkiye revealed remarkable adaptation of Echinococcus canadensis (G6/ G7) in goats - Selcuk, Muhammed Ahmed; Celik, Burcak Aslan; Celik, Figen; Celik, Ozgur Yasar; Ercan, Kerem; Uslug, Muhammet; Simsek, Sami (Elsevier, 2024)
Cystic echinococcosis (CE), caused by Echinococcus granulosus sensu lato (s.l.), represents one of the most significant zoonotic diseases globally, affecting both humans and animals. The objective of this study was to ascertain the prevalence of E. granulosus sensu lato in sheep and goats in a pilot region with a one-year slaughterhouse follow-up period and to determine the genetic differences and haplotypes among sheep, goat, and dog isolates. To this end, the prevalence of CE cysts was determined by monitoring the slaughter of sheep and goats at least three days a week at a slaughterhouse in the Siirt province of T & uuml;rkiye during 2023. Additionally, faecal samples were collected from stray dogs and analysed using both flotation and molecular techniques. The presence of CE cysts was identified in 569 (11.12 %) of the 5119 sheep and 66 (2.31 %) of the 2860 goats after slaughtering. The highest positivity was observed in November (20.39 %), while the lowest was recorded in July (5.62 %). Of the sheep that detected positive, 25 (4.39 %) were less than one year old, while 544 (95.61 %) were older than one year. Of the infected sheep, 26 (4.57 %) were male and 543 (95.43 %) were female. 204 (35.85 %) sheep exhibited fluid-filled CE cysts, 338 (59.40 %) displayed calcification, and 27 (4.75 %) demonstrated the presence of newly developed cysts. The highest positivity was observed in December (5.83 %), while the lowest was recorded in May (0.62 %) in goats. Of the positive goats, two (3 %) were less than one year old, while the remaining 64 (97 %) were older than one year. Of the goats infected with CE cysts, 10 (15.15 %) were male and 56 (84.85 %) were female. Of the cysts, 56.1 % were fluid-filled, 42.4 % were calcified and 1.5 % were newly developed. Following DNA sequence analysis of CE cyst isolates obtained from the slaughterhouse, all 61 sheep sequences were identified as E. granulosus s.s. (G1/G3). Of the 13 goat isolates, seven were identified as E. granulosus s.s. (G1/G3), while the remaining six were classified as E. canadensis (G6/ G7). The centrifugal flotation method was employed to detect the presence of Isospora spp. oocysts in eight dogs, Toxocara canis and hookworm eggs in three dogs each, and Dipyllidium caninum eggs in one dog. A total of 54 dog faeces were examined. No Taeniid eggs were observed in any of the dogs. Following PCR analysis of the mt-CO1 gene region in the dog faecal samples, four samples were positive for a 875 bp band. Only one of these bands was suitable for sequence analysis, which confirmed it as E. granulosus s.s. (G1/G3).
Keywords: Echinococcus granulosus; Sheep; Goat; Dog; Prevalance; Genotyping